2018
DOI: 10.1186/s12974-018-1323-1
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate receptor subtype 3 (S1P3) contributes to brain injury after transient focal cerebral ischemia via modulating microglial activation and their M1 polarization

Abstract: BackgroundThe pathogenic roles of receptor-mediated sphingosine 1-phosphate (S1P) signaling in cerebral ischemia have been evidenced mainly through the efficacy of FTY720 that binds non-selectively to four of the five S1P receptors (S1P1,3,4,5). Recently, S1P1 and S1P2 were identified as specific receptor subtypes that contribute to brain injury in cerebral ischemia; however, the possible involvement of other S1P receptors remains unknown. S1P3 can be the candidate because of its upregulation in the ischemic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 60 publications
3
83
0
Order By: Relevance
“…S1P is the ligand for S1PR and has been identified to bind to S1PR1, S1PR2 and S1PR3 to trigger neuroinflammatory responses in ischemic stroke (Fig. 2) (89)(90)(91). an in vitro study reported that upon the addition of S1P to the culture medium of primary microglia, the expression levels of IL-17 were increased (31).…”
Section: Nrfmentioning
confidence: 99%
See 1 more Smart Citation
“…S1P is the ligand for S1PR and has been identified to bind to S1PR1, S1PR2 and S1PR3 to trigger neuroinflammatory responses in ischemic stroke (Fig. 2) (89)(90)(91). an in vitro study reported that upon the addition of S1P to the culture medium of primary microglia, the expression levels of IL-17 were increased (31).…”
Section: Nrfmentioning
confidence: 99%
“…This culminated in an increase in the expression levels of S1P and M1 microglial markers, CD11b, cd16, cd32, cd86, TnF-α and il-1β, as well as an increased infarct volume and neurological deficit (81). CAY10444, an inhibitor of S1Pr3, and PF-543, an inhibitor of Sphk1, were identified to partially reverse the result to increase the expression levels (31,91); however, Qin et al (71) described opposing results, following the observation that Fingolimod, an S1Pr agonist, inhibited M1 microglia-induced neuroinflammation and shift microglia toward M2 polarization through regulating STaT3 signaling in a BcaS-induced model of ischemic stroke. Therefore, additional studies are required to determine the role of S1P and S1Prs in the regulation of microglia polarization following ischemic stroke.…”
Section: Nrfmentioning
confidence: 99%
“…The effect of kellerin on the NLRP3 signaling pathway may be responsible for its function in regulating microglial polarization. MAPK signaling pathways also mediate microglial polarization during cerebral ischemia (Gaire, Bae, & Choi, ; Gaire, Song, & Choi, ; Xiang et al, ). MAPKs function as three‐tiered kinase cascades leading to the activation of the effector kinases ERK, p38, and JNK (Kondreddy et al, ; Lanna et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…S1P signaling in TAMs leads to increased cellular proliferation, and enhanced production of different pro-inflammatory cytokines (such as TNF-α and IL-1β and IL-17) and nitric oxide, and this signaling is inhibited by SphK1 inhibition or gene knockout of this enzyme [149,253]. S1P1-3 receptor subtypes were identified as relevant in S1P signaling in transient cerebral ischemia [253][254][255][256]. In addition, S1P regulates M1/M2 polarization toward brain damage as a pathogenesis of cerebral ischemia.…”
Section: S1p In the Cancer Microenvironment Promotes Immune-evasionmentioning
confidence: 99%